2020
DOI: 10.1590/s1519-99402121262020
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis in sheep supplemented with detoxified castor bean (Ricinus communis L.) as a replacement for soybean meal

Abstract: The objective was to evaluate the effect of replacing soybean meal with the detoxified castor bean cake on testicular morphometry and spermatogenesis of sheep. Were used 24 uncastrated, 9-month old sheep weighing 29±0.8 kg they were randomly distributed among three treatments: T1 = 0%, T2 = 50%, and T3 = 100% substitution of soybean meal with detoxified castor bean cake. The animals were fed with Aruana grass pastage (Panicum maximum ‘Aruana’) and a ration for 90 days. After slaughtering, the testicles were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The reduced PL count in the group treated with 10% cocoa meal does not seem to have a biological justification. It is common for degenerative processes to occur in germline cells (Amann, 1962), and PL are usually the most vulnerable (Andreussi et al, 2014;Rocha et al, 2020). However, for this reasoning to be valid, the groups treated with higher cocoa meal concentrations would also have to exhibit reduced PL levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced PL count in the group treated with 10% cocoa meal does not seem to have a biological justification. It is common for degenerative processes to occur in germline cells (Amann, 1962), and PL are usually the most vulnerable (Andreussi et al, 2014;Rocha et al, 2020). However, for this reasoning to be valid, the groups treated with higher cocoa meal concentrations would also have to exhibit reduced PL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested a common variation in the spermatogenesis of small ruminants (Leal et al, 2004;Sousa et al, 2014;Rocha et al, 2020), which can be justified by degenerative alterations or nutritional (Souza et al, 2014) and genetic factors (Andreussi et al, 2014). This variation may influence the dynamics of spermatogenesis growth waves (Perey et al, 1961), thus promoting a wide range of said waves within the species and even in different seminiferous tubules of the same animal.…”
Section: Discussionmentioning
confidence: 99%